A CALL FOR A NEW INTERCULTURAL COMPETENCE PLAYBOOK IN MEDIATING SOCIAL TRANSFORMATION - Gowers, Rory (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2023)
Every culture is in conflict; conflict is endemic in the process of culture metamorphosis. This paper examines the paradox that conflict is intrinsic to every culture, yet there is little attention to the ‘culture’ norms in resolving that conflict. There are conflicts within cultures and there are conflicts between cultures. The pioneering scholarship on national cultural traits, by original thinkers such as Hofstede and Ting- Toomey in the 1990s, assisted negotiation and dispute resolution and provided a foundation for cultural differentiation. But much has changed in intercultural understanding since then. We are now aware of enormous variations in values, styles, and customs in defined cultures. Today in the 2020’s we are fast becoming a more global interdependent society with high cultural diversity, declining Western power, and rising Asian-led world order in a new era of commercial influence, high-speed digital robotics, and artificial intelligence.We are in an unprecedented global pandemic where cultural norms and expectations are under threat, in individualistic and collectivist cultures. We face existential threats from climate change and environmental catastrophes. We need a new mediator playbook for effective intercultural negotiation and issue resolution.